Shame and compulsive behaviours - Hooper, Megan (University of the Witwatersrand, Johannesburg, 1996)
The area of shame, in psychology, has become increasingly popular in recent years. Despite a great richness of theoretical literature, there is, unfortunately, a dearth of actual research on shame. This study has sought to empirically investigate the relationship between shame and three compulsive behaviours, namely, alcohol dependence, drug dependence and disordered eating. Relations between shame and alcohol dependence, and shame and drug dependence have already been established in the research literature. This study sought to validate these relationships and to extend the research in the area to establish a link between shame and disordered eating. Cook's Internalised Shame Scale was used to assimilate shame, whilst Millon's Clinical Multiaxial Inventory was used to assess drug and alcohol dependence. Disordered eating was assessed by using the Eating Attitudes Test. Pearson's Product Moment Correlations were computed, and regression analyses were conducted, it was found that shame was significantly correlated with alcohol dependence, drug dependence and disordered eating, and that shame predicted 33% of the variation in alcohol dependent behaviour, 36% of the variation in drug dependent behaviour, and 30% of the variation in disordered eating. Within the methodology used it was not possible to establish causality. However, it was possible to contextualise these results within the literature, and suggest possible explanations. From within the literature on shame it was suggested that shame is linked to alcohol abuse and drug abuse as well as to disordered eating, and that the relationship is one of circular causality. Shame is consequent on these behaviours but these behaviours also attempt to reduce shame and are intended to be self soothing, and containing of the uncomfortable feelings attached to an inadequate sense of self. Limitations of the study, and suggestions for future research were examined.
95 leaves.
Keywords: Shame; Compulsive behavior -- Psychological aspects